2017
DOI: 10.3390/molecules22050692
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Components from Qingwen Baidu Decoction against LPS-Induced Acute Lung Injury in Rats

Abstract: Qingwen Baidu Decoction (QBD) is an extraordinarily “cold” formula. It was traditionally used to cure epidemic hemorrhagic fever, intestinal typhoid fever, influenza, sepsis and so on. The purpose of this study was to discover relationships between the change of the constituents in different extracts of QBD and the pharmacological effect in a rat model of acute lung injury (ALI) induced by lipopolysaccharide (LPS). The study aimed to discover the changes in constituents of different QBD extracts and the pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Angoroside C (Figure 1 ) is a representative phenylpropanoid glycoside (PhG) compound isolated from Scrophularia ningpoensis Hemsl ( Li et al, 2000 ; Wagner et al, 2011 ). Which possesses the ability to reduce blood pressure ( Liu et al, 2015 ), and has anti-inflammatory ( Díaz et al, 2004 ), anti-platelet aggregation ( Cano et al, 1990 ), hepatoprotection ( Huang et al, 2004 ; Morikawa et al, 2010 ), and hypoglycemic properties ( Tian et al, 2017 ), as well as being able to reduce pulmonary oedema ( Zhang et al, 2017 ). Furthermore, according to the continuous series of in-depth studies by Gu Weiliang on Radix Scrophulariae ( Gu et al, 2010 ; Huang et al, 2012 ), the results showed that angoroside C has beneficial effects against ventricular remodeling, and the mechanism is likely to be related to decreasing the level of Ang II, attenuating the mRNA expressions of endothelin 1 (ET-1) and transforming growth factor β1 (TGF-β1) ( Gu et al, 2015 ), which is effective in postponing heart failure for patients with cardiovascular illness.…”
Section: Introductionmentioning
confidence: 99%
“…Angoroside C (Figure 1 ) is a representative phenylpropanoid glycoside (PhG) compound isolated from Scrophularia ningpoensis Hemsl ( Li et al, 2000 ; Wagner et al, 2011 ). Which possesses the ability to reduce blood pressure ( Liu et al, 2015 ), and has anti-inflammatory ( Díaz et al, 2004 ), anti-platelet aggregation ( Cano et al, 1990 ), hepatoprotection ( Huang et al, 2004 ; Morikawa et al, 2010 ), and hypoglycemic properties ( Tian et al, 2017 ), as well as being able to reduce pulmonary oedema ( Zhang et al, 2017 ). Furthermore, according to the continuous series of in-depth studies by Gu Weiliang on Radix Scrophulariae ( Gu et al, 2010 ; Huang et al, 2012 ), the results showed that angoroside C has beneficial effects against ventricular remodeling, and the mechanism is likely to be related to decreasing the level of Ang II, attenuating the mRNA expressions of endothelin 1 (ET-1) and transforming growth factor β1 (TGF-β1) ( Gu et al, 2015 ), which is effective in postponing heart failure for patients with cardiovascular illness.…”
Section: Introductionmentioning
confidence: 99%
“…In acute lung injury, the continued and uncontrolled inflammatory response results in PMN infiltration into the alveolar and pulmonary edema, thereby damaging the respiratory function. And reducing the quantity and infiltration of activated PMNs was beneficial to acute lung injury [ 5 ]. Evidence about PMNs' role in diseases has been mentioned in some research.…”
Section: Introductionmentioning
confidence: 99%
“…To explore the underlying constituents of QBD, we analyzed the constituents and related pharmacology by PCA method. The results showed that EG, PGG, galloyl paeoniflorin, mudanpioside C, and harpagoside can effectively protect against ALI 11. On the basis of the previous studies, we further verify the effects of EG and PGG on ALI in rats.…”
Section: Discussionmentioning
confidence: 65%
“…The HPLC chromatogram elution profile was as follows: 2% A (0–10 minutes); 2%–7% A (10–20 minutes); 7%–9% A (20–40 minutes); 9 and 10% A (40–50 minutes); 10%–16% A (50–60 minutes); 16 and 17% A (60–65 minutes); 17%–20% A (65–80 minutes); and 20%–24% A (80–112 minutes). The flow rate of mobile phase was 1.0 mL/min, and the UV spectra were 254 nm 11…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation